Optimzing the teaching of english suprasegmetals to spanish speakers - Chela-Flores, Bertha (Lenguas Modernas, 2017)
The purpose of this paper is to examine, in the light of relevant research, pedagogical experience, and an understanding of native speaker competence, basic issues of English rhythm and intonation which are important to communicative meaning. These features, in tum, will serve to determine a basic system to be used as a starting point in instruction. To this effect, an examination is made of specific issues in the rhythm and intonation of English and Spanish, with special reference to declarative sentences in marked and unmarked utterances. The teaching technique suggested will force learners to focus on the phonological pattems without the normal segments and sequences with which they co-occur, so that such learners can more accurately discriminate the auditory effects of the suprasegmental features.